1996
DOI: 10.1161/01.str.27.2.252
|View full text |Cite
|
Sign up to set email alerts
|

Sleep-Disordered Breathing and Poor Functional Outcome After Stroke

Abstract: SDB accompanied by arterial oxyhemoglobin desaturation is common in patients undergoing rehabilitation after stroke and is associated with higher mortality at 1 year and lower BI scores at discharge and at 3 and 12 months after stroke. SDB may be an independent predictor of worse functional outcome. Obstructive sleep apnea appeared to be the most common form of SDB, and the frequent history of snoring suggests that SDB preceded the stroke in most patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
223
3
12

Year Published

2000
2000
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 364 publications
(257 citation statements)
references
References 38 publications
10
223
3
12
Order By: Relevance
“…Dyken et al 218 noted that patients after stroke have a high prevalence of OSA and that those stroke patients with OSA had a markedly diminished poststroke survival. Similar findings regarding survival and limited rehabilitation success 219,220 have been reported by other investigators. Direct studies of the interaction between sleep apnea and rehabilitation outcome after stroke that used overnight pulse oximetry to evaluate the respiratory disturbance index suggested that hypoxic events during sleep predicted poorer recovery, especially in patients with poor function at admission.…”
Section: Treatment Of Osa: Effects On Strokesupporting
confidence: 91%
“…Dyken et al 218 noted that patients after stroke have a high prevalence of OSA and that those stroke patients with OSA had a markedly diminished poststroke survival. Similar findings regarding survival and limited rehabilitation success 219,220 have been reported by other investigators. Direct studies of the interaction between sleep apnea and rehabilitation outcome after stroke that used overnight pulse oximetry to evaluate the respiratory disturbance index suggested that hypoxic events during sleep predicted poorer recovery, especially in patients with poor function at admission.…”
Section: Treatment Of Osa: Effects On Strokesupporting
confidence: 91%
“…Mechanisms have been postulated to account for possible increased atherogenesis in OSAS [26], and it has recently been reported that patients with coexisting CHD and OSAS are at increased risk of apnoeaassociated ischaemic events [27]. An association of snoring and OSAS is also reported with stroke and possibly stroke prognosis [28], though studying patients following stroke is made difficult by the fact that stroke itself may induce or worsen OSAS. The findings in this paper are in general agreement with these previous reports but do not help distinguish a separate risk from OSAS independent of other confounding variables.…”
Section: Discussionmentioning
confidence: 99%
“…But in OSA patients who are said to be nondippers, they have absent fall in nocturnal BP (Leung et al, 2001). Studies also suggest an increase in the risk of myocardial infarction and stroke in untreated OSAHS (Good et al, 1996;Leung et al, 2001;Leung, 2009), Bblockers have been reported to be the most effective among antihypertensive agents, in lowering daytime BP in hypertensive OSA patients as sympathetic overactivity is involved. However antihypertensive medications have little effect on nocturnal BP in OSA, possibly because they do not reduce OSA (Kraiczi et al, 2000).…”
Section: Associated Featuresmentioning
confidence: 99%